ROLE OF JALAUKAVACHARANA IN NETRA ROGA - Dr, *Anjali; Sharma, Gunjan; Bamola, Poonam (International Journal of Ayurveda and Pharma Research, 2016)
Raktamokshana (bloodletting) is a parasurgical procedure directed for the treatment of Raktajaroga (blood-borne diseases) along with many surgical diseases. Method of removing vitiated blood from body using Jalauka is considered as the most easier and convenient method. It is considered as most unique and most effective method of bloodletting. It is safely indicated in all mankind including the patients having poor threshold to pain. Application of leech mitigates diseases in eyes.Jalukavacharana has the property to subside immediately the pain, swelling, burning sensation and redness. Now days environment is being highly polluted, due to which there is increased chances of infections in the eyes. Prevalance of eye diseases is very high but medical science have limited number of drugs. Mast cell stabilizers, NSAIDs and topical corticosteroids are the treatment options, but only symptomatic relief is the outcome. There is no curative treatment but only palliative treatment. On the other hand, drug sensitivity, increasing resistance, preservative-induced dry eye as well as the complications of the corticosteroids, for example, cataract, glaucoma, and increased risk of bacterial and fungal infections restrict the long-term use of these medicines. In view of magnitude of problem, the discomfort it causes to the patient and the cost of treatment, there is a need of develop of a treatment which is free of side effects, cheaper and has a significant effect in relieving the symptoms of the patients